Genetic technology - Sabo, Linda; Faas, Lisa; Sourbeer, Dan; Insight Media (Firm); Palomar College. Educational Television (New York : Insight Media, 1999)
Explores topics in genetic technology, explaining how restriction enzymes are used and discussing probes, gel electrophoresis, steps in a DNA fingerprint, and uses for DNA fingerprinting
Palomar College Educational Television
Cameras, Chris Maue, Denise Galvan, Salvador Orozco, Antoinette Griffith, Jon Phail ; videotape and editing, Lia Piancone ; video photojournalist, Warren Wolfe
Instructor, Dan Sourbeer
DVD
Keywords: Genetic engineering